Effects of direction of rotation in continuous and discontinuous 8 hour shift systems. Issue 10 (1st October 2000) - Tucker, Philip; Smith, Lawrence; Macdonald, Ian; Folkard, Simon
Abstract : OBJECTIVES: Previous research has produced conflicting evidence on the relative merits of advancing and delaying shift systems. The current study assessed the effects of the direction of shift rotation within 8 hour systems, upon a range of measures including sleep, on shift alertness, physical health, and psychological wellbeing. METHODS: An abridged version of the standard shiftwork index which included retrospective alertness ratings was completed by four groups of industrial shiftworkers on relatively rapidly rotating 8 hour systems (n=611). Two groups worked continuous systems that were either advancing or delaying; the other two groups worked discontinuous systems that were either advancing or delaying. RESULTS: Few effects were found of direction of rotation on chronic measures of health and wellbeing, even when the systems incorporated "quick returns" (a break of only 8 hours when changing from one shift to another). This was despite the use of measures previously shown to be sensitive to the effects of a broad range of features of shift systems. However, advancing continuous systems seemed to be associated with marginally steeper declines in alertness across the shift ( F (3, 1080)=2.87, p<0.05). They were also associated with shorter sleeps between morning shifts ( F (1, 404)=4.01, p<0.05), but longer sleeps between afternoons ( F (1, 424)=4.16, p<0.05). CONCLUSIONS: The absence of negative effects of advancing shifts upon the chronic outcome measures accorded with previous evidence that advancing shifts may not be as harmful as early research indicated. However, this interpretation is tempered by the possibility that difficult shift systems self select those workers most able to cope with their deleterious effects. The presence of quick returns in advancing continuous systems seemed to impact upon some of the acute measures such as duration of sleep, although the associated effects on alertness seemed to be marginal.